2008
DOI: 10.1186/bf03353145
|View full text |Cite
|
Sign up to set email alerts
|

Imaging heterogeneous velocity structures and complex aftershock distributions in the source region of the 2007 Niigataken Chuetsu-oki Earthquake by a dense seismic observation

Abstract: The velocity structure and accurate aftershock distributions in the source region of the 2007 Niigataken Chuetsu-oki Earthquake (thrust type) are obtained by inverting the arrival times from 848 aftershocks observed by a dense seismic network deployed immediately after the mainshock (8 h later). Both the detailed velocity structure and the accurate aftershock distribution show lateral heterogeneity along the fault strike. In the northeast area, aftershocks are aligned along both the NW-and SE-dipping planes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 19 publications
3
56
0
1
Order By: Relevance
“…Similar patterns of aftershocks were also observed by Sakai et al (2007), Shinohara et al (2008), and Yukutake et al (2008). Based on the configuration of the mainshock hypocenter and the aftershock distribution, Kato et al (2008) speculated that rupture of the mainshock may have initiated on the NW-dipping plane and then transferred to the conjugated fault plane (i.e., the SE-dipping plane).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar patterns of aftershocks were also observed by Sakai et al (2007), Shinohara et al (2008), and Yukutake et al (2008). Based on the configuration of the mainshock hypocenter and the aftershock distribution, Kato et al (2008) speculated that rupture of the mainshock may have initiated on the NW-dipping plane and then transferred to the conjugated fault plane (i.e., the SE-dipping plane).…”
Section: Introductionsupporting
confidence: 57%
“…However, the aftershock distribution may not be so simple that a single fault plane would be identified. Kato et al (2008) inverted the arrival times from aftershocks observed by a dense seismic network deployed immediately after the mainshock and Copyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the former two groups of researchers found that aftershocks in the northern region were distributed along both the northwestwardand southeastward-dipping planes. Furthermore, Kato et al (2008) revealed a complex aftershock distribution with numerous conjugated fault planes in the central aftershock region, which corresponds to the F-F cross-section in Fig. 3.…”
Section: Hypocenter Locationsmentioning
confidence: 99%
“…Yukutake et al (2008) estimated aftershock distributions of the 2007 earthquake by applying a double-difference method (Waldhauser and Ellsworth, 2000) to both manually picked and waveform cross-correlation data which were observed at permanent online stations. Kato et al (2008) determined the velocity structure and aftershock distributions of the 2007 earthquake by applying a double-difference tomography method (Zhang and Thurber, 2003) to arrival times observed by a dense seismic network deployed immediately after the mainshock. The aftershock distributions determined in the above two studies present a sharper image than we obtained in our present study and reveal several discrete fault segments.…”
Section: Hypocenter Locationsmentioning
confidence: 99%
See 1 more Smart Citation